Efektivitas Sistem Pemidanaan Terhadap Residivis Tindak Pidana Narkotika di Kota Gorontalo - Putra Krisna Suryantoro (Judge : Jurnal Hukum, 2025)
This study examines the challenges of the effectiveness of the criminal justice system in reducing drug-related recidivism in Gorontalo City using a juridical-sociological approach. The main focus of the research is to identify social, economic, and stigma factors that serve as root causes of high recidivism rates, as well as to evaluate the implementation of rehabilitation and social reintegration for former drug offenders. The methods used include in-depth interviews with inmates, correctional officers, family members, and law enforcement officials, complemented by a literature review on criminal policy and relevant legal theories. The results of the study show that the criminal justice system in Gorontalo is still dominated by a repressive approach, which emphasizes physical punishment and technical training without adequate psychological support, making it ineffective in breaking the cycle of recidivism. Approximately 40% of former prisoners experience mental health issues, but the counseling services provided are general and not personalized. Social and economic factors, including the stigma attached to former inmates and discrimination, limit their access to employment and business opportunities, forcing them to return to old environments that are prone to crime. This study underscores the urgency of reforming the criminal justice system by integrating psychosocial rehabilitation programs, economic empowerment, and stigma reduction through public education. Collaboration between legal instruments, government, society, and families is essential to create inclusive and sustainable social reintegration. With this paradigm shift, the criminal justice system is expected to play a more optimal role as a tool for rehabilitation and social protection that can significantly reduce drug recidivism rates in Gorontalo City.